479. Trends in C. difficile Incidence, Mortality, and NAP1/027 Strain in the Population of Monroe County, New York. (26th November 2018) - Hatwar, Trupti; Tsay, Rebecca; Nelson, Deborah; Felsen, Christina B; Dumyati, Ghinwa
Abstract: Background: Increases in the C. difficile infection (CDI) incidence, severity and mortality were reported in the early 2000s due to the emergence of the NAP1/027 strain. We evaluated the trends in incidence, mortality, hospitalization, and the prevalence of NAP1/027 strain in Monroe County, New York. Methods: We conducted population and laboratory-based surveillance for CDI from 2011 to 2016 as part of the CDC Emerging Infections Program. An incident CDI case is defined as a positive C. difficile stool specimen from a resident of the county aged >1 year with no positive test in the prior 8 weeks. All the laboratories in our catchment area used nucleic acid amplification for diagnosis starting in 2011 as part of single or 2-step algorithm. A convenience sample of specimens were cultured and underwent molecular characterization. Mortality data was obtained via vital statistics databases and medical chart abstraction. Hospitalization within 2 days before to 7 days of diagnosis was collected. Results: We identified 9189 incident CDI cases between 2011 and 2016. The CDI incidence decreased from 241 in 2011 to 175 cases per 100, 000 persons in 2016, with the largest decrease among older adults aged ≥85 years. Similarly, the 30-day mortality rates decreased, with the largest decrease among persons aged ≥85 years: from 310 cases to 169 cases per 100, 000 population (Figure 1). The percentage of isolates due to NAP1/027 decreased from 20.3% in 2011 to 6.5% in 2016. There was no decrease in the proportion of cases that died within 7 (range: 2% to 3%) and 30 days (range: 7% to 8%) and no decrease in the proportion of patients hospitalized after their CDI diagnosis (range: 34% to 40%). These findings are similar in persons aged ≥85 years. Conclusion: From 2011 to 2016, the CDI incidence and mortality decreased concurrently with a decrease in the percentage of infections due to the NAP1/027 strain. Although NAP1/027 is known to be associated with more severe outcomes, we did not observe a reduction in the proportion of cases that died or the proportion of cases that were hospitalized. Disclosures: G. Dumyati, Seres: Scientific Advisor, Consulting fee.